Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
12(x - 6) = 4x + 12
12x - 72 = 4x + 12
12x - 4x = 12 + 72
8x = 84
x = 84 : 8
x = 21/2
Đề: Tìm x
\(12\times\left(x-6\right)=4\times x+12\)
\(12\times x-12\times6=4\times x+12\)
\(12\times x-72=4\times x+12\)
\(12\times x-4\times x=72+12\)
\(8\times x=84\)
\(x=84:8\)
\(x=10,5\)
\(12\times\left(x-6\right)=4\times x+12\)
\(12\times x-72=4\times x+12\)
\(12\times x-4\times x=12+72\)
\(8\times x=84\)
\(x=10,5\)
(3/7 + x) : 4/9 = 12/13
3/7 + x = 12/13 . 4/9
3/7 + x = 16/39
x = 16/39 - 3/7
x = -5/273
\(\left(\frac{3}{7}+x\right):\frac{4}{9}=\frac{12}{13}\)
\(\frac{3}{7}+x=\frac{12}{13}\cdot\frac{4}{9}\)
\(\frac{3}{7}+x=\frac{160}{117}\)
\(x=\frac{160}{117}-\frac{3}{7}\)
\(x=\frac{769}{819}\)
\(1-x=\frac{29}{12}+\frac{32}{8}\)
\(\Rightarrow1-x=\frac{77}{12}\)
\(\Rightarrow x=1-\frac{77}{12}=\frac{-65}{12}\)
\(\frac{31}{8}.x-\frac{11}{4}=\frac{42}{12}.\frac{10}{8}-\frac{1}{3}\)
\(\Rightarrow\frac{31}{8}.x-\frac{11}{4}=\frac{35}{8}-\frac{1}{3}\)
\(\Rightarrow\frac{31}{8}.x-\frac{11}{4}=\frac{97}{24}\)
\(\Rightarrow\frac{31}{8}.x=\frac{97}{24}+\frac{11}{4}=\frac{163}{24}\)
\(\Rightarrow x=\frac{163}{24}:\frac{31}{8}=\frac{163}{93}\)
Tính nhanh:
36 x 28 + 4 x 9 x 82 + 64 x 69 + 8 x 41 x 8
= 36 x 28 + ( 4 x 9 ) x 82 + 64 x 69 + ( 8 x 8 ) x 41
= 36 x 28 + 36 x 82 + 64 x 69 + 64 x 41
= 36 x ( 28 + 82 ) + 64 x ( 69 + 41 )
= 36 x 110 + 64 x 110
= 110 x ( 36 + 64 )
= 110 x 100
= 11000
^^ Học tốt nhé!
Ta có : (x + 3) + (x + 6) + (x + 9) + ...... + (x + 30) = 330
<=> (x + x + x + ...... + x) + ( 3 + 6 + 9 + ...... + 30 ) = 330
<=> 10x + 165 = 330
=> 10x = 2
=> x = 1/5
(x+x+x+..+x)+(3+6+9+...+30)
10x+165=330
10x=330-165
10x=165
x=165/10
x=16,5
\(6x\frac{7}{8}+\frac{9}{10}:\frac{5}{3}\)
=\(\frac{42}{8}+\frac{9}{10}x\frac{3}{5}\)
=\(\frac{21}{4}+\frac{21}{50}\)
=\(\frac{525}{100}+\frac{42}{100}\)
=\(\frac{567}{100}\)
=\(\frac{4}{5}:2x\frac{8}{9}:4\)
=\(\frac{4}{5}x\frac{1}{2}x\frac{8}{9}x\frac{1}{4}\)
=\(\frac{4x1x2x4x1}{5x2x9x4}\)
=\(\frac{4}{45}\)
( X - 39 ) x 4 : 9 = 12
( X - 39 ) x 4 = 12 x 9
( X - 39 ) x 4 = 108
X - 39 = 108 : 4
X - 39 = 27
X = 27 + 39
X = 66
\(\left(x-39\right).4:9=12\)
\(\left(x-39\right).4=12.9\)
\(\left(x-39\right).4=108\)
\(x-39=108:4\)
\(x-39=27\)
\(x=27+39\)
\(x=66\)